Diverse Roles of Antibodies in Antibody–Drug Conjugates - Aiko Yamaguchi; H. Charles Manning (Pharmaceuticals)
The emergence of antibody–drug conjugates (ADCs) has transformed the treatment landscape of a variety of cancers. ADCs typically consist of three main components: monoclonal antibody, chemical linker, and cytotoxic payload. These integrated therapeutic modalities harness the benefits of each component to provide a therapeutic response that cannot be achieved by conventional chemotherapy. Antibodies play roles in determining tumor specificity through target-mediated uptake, prolonging the circulation half-life of cytotoxic payloads, and providing additional mechanisms of action inherent to the original antibody, thus significantly contributing to the overall performance of ADCs. However, ADCs have unique safety concerns, such as drug-induced adverse events related to the target-mediated uptake of the ADC in normal tissues (so-called “on-target, off-tumor toxicity”) and platform toxicity, which are partially derived from limited tumor uptake of antibodies. Identifying suitable target antigens thus impacts the clinical success of ADCs and requires careful consideration, given the multifaceted aspects of this unique treatment modality. This review briefly summarizes the representative roles that antibodies play in determining the efficacy and safety of ADCs. Key considerations for selecting suitable cell surface target antigens for ADC therapy are also highlighted.